(1009) The Effects of Changes in Location of Production on A.R.E. Cotton Yields آثار التغيرات في موقع الإنتاج على انتاج محصول القطن فى جمهورية مصر العربية - Kamal El-Ganzouri. (INP., 2020)
Agricultural productivity in the Arab Republic of Egypt has witnessed a significant increase over the past two decades, particularly in major crops such as cotton. This paper examines the factors contributing to this growth, including changes in production locations, technological advancements, favorable weather conditions, and economic incentives such as pricing policies. So, The study highlights the importance of integrating economic, environmental, and technological perspectives to enhance agricultural development in Egypt.